A Study through the lens of Munāsabāt al-Qur'ān: The Correlation between the meanings of Q. 1:7 and Q. 2:1-2 - Ilzam Hubby Dzikrillah Alfani; Asep Ahmad Fathurrohman; Muhammad Ruhiyat Haririe; Fitri Meliani; Rizki Maulana Putra (Jurnal Ushuluddin, 2026)
This study examines the semantic correlation between Q. 1:7 and Q. 2:1-2 using a thematic exegesis (tafsir maudhu'i) approach enriched with semantic-hermeneutic analysis. It aims to reveal the profound conceptual and structural relationship between the supplication for guidance (aṣ-ṣirāṭ al-mustaqīm) in Surah Al-Fatihah and the affirmation of the Qur'an as guidance (hudan lil-muttaqīn) in Surah Al-Baqarah. The applied research method integrates linguistic analysis of key terms, a study of munasabah (inter-verse correlation), and a comparison of classical and contemporary exegeses, incorporating Toshihiko Izutsu's semantic theory and Fazlur Rahman's philosophical hermeneutics. The findings reveal that the two verses form a dialectical relation characterized as a divine question and answer (su'al wa jawāb).. Surah Al-Fatihah functions as a universal preamble (muqaddimah kuliyyah) formulating the fundamental principles of Islamic teachings, while Q. 2:1-2 acts as its operational elaboration (tafsīl 'amali). This relationship reflects a transcendental communication between the servant and the Creator, manifested through three interconnected layers of meaning: the theological layer (encompassing monotheism and its implementation), the anthropological layer (explaining the balance of the human role as servant and vicegerent), and the epistemological layer (integrating revelation as guidance with God-consciousness as its prerequisite). The implications of these findings are multidimensional, encompassing cognitive transformation (forming a holistic understanding of the Qur'an as a unified system), behavioral transformation (fostering a proactive attitude from seeking to implementing divine guidance), and communal transformation (building a society grounded in the spirituality of Al-Fatihah, actualized within a social order based on Qur'anic guidance) for its readers.